CuO Nanowires-based Electrodes for Glucose Sensors - C. Espro; N. Donato; S. Galvagno; D. Aloisio; S.G. Leonardi; G. Neri (Chemical Engineering Transactions, 2014)
A three electrodes planar electrochemical sensor, based on CuO nanowires growth “in situ” on Cu working electrode, was fabricated by a simple micromachining technique and employed for the non-enzymatic determination of glucose. The microstructural and morphological characteristics of the modified electrode was investigated by XRD and SEM analysis. Cyclic voltammetry and chronoamperometric measurements were performed to evaluate the electrochemical behaviour and the sensing performance of developed sensor towards glucose in alkaline media.